Augmenting the Refutation Text Effect with Analogies and Graphics. Issue 5 (3rd July 2016) - Danielson, Robert W.; Sinatra, Gale M.; Kendeou, Panayiota
Abstract : Refutation texts have been shown to be effective at promoting knowledge revision. It has been suggested that refutation texts are most effective when the misconception and the correct information are co-activated and integrated with causal networks that support the correct information. We explored two augmentations to a refutation text that might enhance the possibility of co-activation, integration, and thus revision: analogies and graphics. Participants (122 college students) were randomly assigned to read one of four experimental texts (refutation text, refutation text+graphic, refutation text+analogy, or refutation text+graphic+analogy). Results showed that refutation text+analogy and refutation text+graphic+analogy were the most successful in promoting revision. Implications for theory and practice are discussed.